The Role of Business Viability Assessments in Microcredit - The Case of Egypt - Fadl, Ahmed (AUC Knowledge Fountain, 2025)
This paper aims to examine the role of business assessments of microfinance applicants and its correlation with microbusiness success as measured in income generated. The key research question of this study is: How do the results of business viability assessments influence the income generated by these businesses? The research methodology used in this study is a combination of both qualitative and quantitative research. Qualitative research includes in-depth interviews with 10 microfinance institutions (MFIs) in five governorates (Al-Sharqia, Assiut, Beni Suef, Giza, and Minya) across Egypt. The quantitative research includes an interviewer-administered questionnaire of 151 micro-business owners who have been in operation for a period of 6 to 12 months. The study found a strong positive correlation between the total score of the business viability assessment and the income level generated by the business. Business assessments can serve as a practical solution in underserved communities where applicants have limited or no collateral, thereby expanding the support capacity of microfinance institutions (MFIs) that currently rely on collateral as their primary risk-mitigation tool. Inputs from in-depth interviews with Egyptian MFIs indicate a strong favoring of those with existing businesses (operating for more than one year) over newly established ones and idea-stage applicants. As a result, individuals without collateral often face higher perceived risk and are less likely to secure microloans. Therefore, this study emphasizes the role of incorporating effective business assessments as a complementary screening measure—one that reduces collateral-based bias and strengthens the potential for business success and subsequent loan repayment.